Can Cohort Replacement Explain Changes in the Relationship Between Age and Homicide Offending? - O’Brien, Robert M. (Journal of quantitative criminology, 2008)
This paper focuses on shifts in the age distribution of homicide offending in the United States. This distribution remained remarkably stable with small but significant changes over a long period of time. Then between 1985 and 1990 the rates of homicide offending doubled for 15-to-19 year olds and increased nearly 40% for 20-to-24 year olds, while the homicide offending rates decreased for those over 30. In addition to this “epidemic of youth homicide,” which lasted through the mid-1990s, there have been systematic changes in the age distribution of homicide in the United States associated with cohort replacement over the past 40 years. We introduce an estimable function approach for estimating the effects of age, period, and cohort. The method allows us to assess simultaneously the impacts of periods and cohorts on the age distribution of homicide offending. We find that although the age curve remains relatively stable, there are shifts in it associated systematically with cohort replacement. Cohort replacement accounts for nearly half of the upturn in youth homicides during the epidemic of youth homicides, but a significant fraction of that upturn is not associated with cohort replacement.